A new karyotype for Rhipidomys (Rodentia, Cricetidae) from Southeastern Brazil - Ana Heloisa Carvalho; Maria Olimpia Lopes; Marta Svartman (Comparative Cytogenetics, 2012)
In this work we present a new karyotype for Rhipidomys Tschudi, 1845 (Cricetidae, Rodentia) from Brazil. Our chromosome analyses included GTG- and CBG-banding patterns, the localization of the nucleolus organizer regions after silver staining (Ag-NORs) and fluorescence in situ hybridization (FISH) with a telomere probe. The new karyotype is composed of 44 chromosomes and has a fundamental number (number of autosomal arms) of 48. Most Rhipidomys species already karyotyped presented similar complements with 2n=44, but their fundamental numbers varied from FN=46 to 80, a variation that has been mainly attributed to pericentric inversions. The comparison of this new karyotype to those of other Rhipidomys already reported allowed us to conclude that it is a distinctive chromosome complement, which can be of great use as a tool for the very complicated taxonomic identification in this genus.